Microbial interspecies interactions: recent findings in syntrophic consortia - Kouzuma, Atsushi; Kato, Souichiro; Watanabe, Kazuya (Frontiers in Microbiology, 2015)
Microbes are ubiquitous in our biosphere, and inevitably live in communities. They excrete a variety of metabolites and support the growth of other microbes in a community. According to the law of chemical equilibrium, the consumption of excreted metabolites by recipient microbes can accelerate the metabolism of donor microbes. This is the concept of syntrophy, which is a type of mutualism and governs the metabolism and growth of diverse microbes in natural and engineered ecosystems. A representative example of syntrophy is found in methanogenic communities, where reducing equivalents, e.g., hydrogen and formate, transfer between syntrophic partners. Studies have revealed that microbes involved in syntrophy have evolved molecular mechanisms to establish specific partnerships and interspecies communication, resulting in efficient metabolic cooperation. In addition, recent studies have provided evidence suggesting that microbial interspecies transfer of reducing equivalents also occurs as electric current via biotic (e.g., pili) and abiotic (e.g., conductive mineral and carbon particles) electric conduits. In this review, we describe these findings as examples of sophisticated cooperative behavior between different microbial species. We suggest that these interactions have fundamental roles in shaping the structure and activity of microbial communities.